Early agriculture in Sri Lanka: New Archaeobotanical analyses and radiocarbon dates from the early historic sites of Kirinda and Kantharodai (Kandarodai). (December 2018) - Murphy, Charlene; Weisskopf, Alison; Bohingamuwa, Wijerathne; Adikari, Gamini; Perera, Nimal; Blinkhorn, James; Horton, Mark; Fuller, Dorian Q.; Boivin, Nicole
Abstract: Archaeobotanical evidence from two Early Historic sites in Sri Lanka, Kantharodai and Kirinda, is reported, providing significant evidence for agricultural diversity beyond the cultivation of rice. These data highlight the potential of systematic archaeobotanical sampling for macro-remains in tropical environments to contribute to the understanding of subsistence history in the tropics. Direct AMS radiocarbon dating confirms both the antiquity of crops and refines site chronologies. Both sites have Oryza sativa subsp. indica rice and evidence of rice crop-processing and millet farming. In addition, phytolith data provide complementary evidence on the nature of early rice cultivation in Sri Lanka. Both Kantharodai and Kirinda possess rice agriculture and a diverse range of cultivated millets ( Brachiaria ramosa, Echinochloa frumentacea, Panicum sumatrense, and Setaria verticillata ). Pulses of Indian origin were also cultivated, especially Vigna radiata and Macrotyloma uniflorum . Cotton ( Gossypium sp.) cultivation is evident from Kirinda. Both sites, but in particular Kirinda, provide evidence for use of the seeds of Alpinia sp., in the cardamom/ginger family (Zingiberaceae), a plausible wild spice, while coconuts ( Cocos nucifera ) were also found at Kirinda.